Views of mathematics teachers regarding creating classroom climate - Kirikkaleli, Nurdan Ozrecberoglu; Serol, Neşe (Intelektual Pustaka Media Utama, 2024)
The fear of failure stops students from thinking logically and processing information in mathematics. Creating an appropriate classroom climate based on every student's ability is crucial to overcoming the prejudices associated with mathematics. In this regard, this study aims to create the best classroom climate approach that will increase interest in mathematics and ensure academic success. For this purpose, mathematicians' views on the classroom climate approach and how they create them were discussed by using qualitative techniques. It was considered that teachers participating in this research are working in 9th grade in state high schools affiliated with the Turkish Republic of North Cyprus Ministry of Education, accepting students through examination. The researchers collected teacher views through a semi-structured interview form and analyzed them using context analysis. The findings showed that teachers were in a hurry to teach and generally paid attention to creating a comfortable classroom climate in which students could express their thoughts and opinions. This situation also revealed a lack of adequate classroom climate approach skills among teachers. Therefore, the classroom climate approaches discussed in this study are expected to make a significant contribution to this field by offering solutions to teachers in creating a supportive classroom climate.